The prediction of colorectal cancer: Perspective of smoking and socioeconomic influence of culture in East Java with SEM analysis - Budianto, Aries; Andarini, Sri; Hariyanti, Tita; Muslihah, Nurul (Nurture, 2024)
Purpose: Colorectal cancer (CRC) is a global malignancy with 10.2% of cases, ranking third in worldwide cancer cases. According to Indonesia Health Research, CRC's prevalence has risen significantly, reaching 1, 8 per mile in 2018, and reports rising cancer cases in the past 5 years. This study explores the relationship model between smoking, socioeconomics, and CRC, considering cultural moderation. Design/Methodology/Approach: Conducted as a retrospective study with 212 respondents, comprising 172 cases of left-sided colorectal cancer (left CRC ) and 40 cases of right-sided colorectal cancer (right CRC) from three cultural areas. Structural Equation Modeling (SEM) employing Warp-PLS was utilized for data analysis. Finding: A significant positive relationship was found between smoking and CRC prediction (β = 0,081, p-value = 0,040). This pattern also applies to socioeconomic status and CRC prediction (β = 0,311, p-value = <0,001). The influence of culture on both relationships is not the same. The relationship between smoking and CRC prediction is not influenced by culture (p-value = 0,318). Conversely, the relationship between socioeconomic status and CRC prediction is influenced by culture (β = 0,078, p = 0,047). Conclusion: Poor smoking habits and weak economic conditions influence the prediction of CRC negatively in East Java Province. Unfavorable cultural practices further worsen the relationship between weak socioeconomic status and poor CRC prediction in East Java Province. Recommendations suggest that preventing adverse CRC outcomes can be achieved through smoking cessation and improving socioeconomic conditions. Preventive efforts to enhance socioeconomic conditions should consider local cultural nuances. Research limitation: This research is limited to a population group in East Java Province, Indonesia, divided into three cultural areas: Mataraman, Arek, and Pendalungan.